CAPN10 SNP-19 is Associated with Susceptibility of Type 2 Diabetes Mellitus: A Javanese Case-control Study - Yanuarita Tursinawati; Rifqi Fauzan Hakim; Afiana Rohmani; Arum Kartikadewi; Ferry Sandra (The Prodia Education and Research Institute (PERI), 2020)
BACKGROUND: The health data of Central Java, Indonesia showed that diabetes mellitus (DM) was the second most increasing non-communicable disease in the province. More than 20 genes have been reported to be associated with DM. Calpain-10 (CAPN10) polymorphism has been reported to be associated with Type 2 Diabetes Mellitus (T2DM). However, the association between CAPN10 single nucleotide polymorphism (SNP)-19 and T2DM among Javanese ethnics has never been reported. Therefore, this study was conducted to investigate the association.METHODS: After fasting for 8 hours, blood samples were drawn from veins of 107 T2DM and 107 non diabetic subjects. A half of the drawn blood was collected for identification of CAPN10 SNP-19, and another half for measuring triglycerides and fasting blood glucose (FBG). Identification of CAPN10 SNP-19 was performed with polymerase chain reaction (PCR) method, while measurement of triglycerides and FBG with colorimetric enzymatic method.RESULTS: The number of T2DM Javanese subjects with 2R/3R and 3R/3R CAPN10 SNP-19 genotypes was significantly higher than the number of T2DM Javanese subjects with 2R/2R genotype (p=0.002). When each number of 2R/3R and 3R/3R T2DM subjects was compared with the number of 2R/2R T2DM subjects, the number of 2R/3R T2DM subjects was significantly higher than the number of 2R/2R T2DM subjects (p=0.000).CONCLUSION: Javanese subjects with 2R/3R and 3R/3R CAPN10 SNP19 genotypes might have susceptibility of T2DM.KEYWORDS: Calpain-10, CAPN10, polymorphism, type 2 diabetes mellitus, triglycerides, fasting blood glucose